Mechanistic Insights and Potential Use of Siderophores Producing Microbes in Rhizosphere for Mitigation of Stress in Plants Grown in Degraded Land - Singh, Pratiksha; Chauhan, Prabhat K.; Upadhyay, Sudhir K.; Singh, Rajesh Kumar; Dwivedi, Padmanabh; Wang, Jing; Jain, Devendra; Jiang, Mingguo (Frontiers in Microbiology, 2022)
Plant growth performance under a stressful environment, notably in the agriculture field, is directly correlated with the rapid growth of the human population, which triggers the pressure on crop productivity. Plant perceived many stresses owing to degraded land, which induces low plant productivity and, therefore, became a foremost concern for the future to face a situation of food scarcity. Land degradation is a very notable environmental issue at the local, regional and global levels for agriculture. Land degradation generates global problems such as drought desertification, heavy metal contamination, and soil salinity, which pose challenges to achieving many UN Sustainable Development goals. The plant itself has a varied algorithm for the mitigation of stress arising due to degraded land; the rhizospheric system of the plant has diverse modes and efficient mechanisms to cope with stress by numerous root-associated microbes. The suitable root-associated microbes and components of root exudates interplay against stress and build adaptation against stress-mediated mechanisms. The problem of iron-deficient soil is increasing owing to increasing degraded land across the globe, which hampers plant growth productivity. Therefore, in context to tackle these issues, the present review aims to identify plant stress status owing to iron-deficient soil and its probable eco-friendly solution. Siderophores are well-recognized iron-chelating agents, produced by numerous microbes, and are associated with the rhizosphere. These siderophore-producing microbes are eco-friendly and sustainable agents, which may be managing the plant stress in degraded land. The review also focuses on the molecular mechanism of siderophores and their chemistry, cross-talk between plant root and siderophores producing microbes to combat plant stress, and utilization of siderophores in plant growth under degraded land.